Theory-based mHealth targeting fathers and mothers to improve exclusive breastfeeding: a quasi-experimental study - Kidane Tadesse Gebremariam; Afework Mulugeta; Danielle Gallegos (BMC, 2023)
Abstract Background Exclusive breastfeeding remains sub-optimal in low-income countries contributing to infant mortality. Mobile health (mHealth) interventions, delivered through personal mobile phones, to improve exclusive breastfeeding have shown promise, but very few include fathers or have been applied in low-income countries. The aim of this study was to assess the effectiveness of a SMS-based breastfeeding intervention targeting fathers and mothers in improving exclusive breastfeeding at three months in a low-income country. Methods A quasi-experimental study was carried out with couples in their last trimester of pregnancy, at health centers, Mekelle, Tigray. This study was conducted from September 2018 to March 2019. The SMS-based intervention delivered a total of 16 SMS text messages to two arms: mothers-and-fathers, and mothers-only with the third group acting as the control. The main outcome measure was exclusive breastfeeding at months one, two and three after birth. Result There were no significant differences in exclusive breastfeeding at month one between the three, mothers-and-fathers (95.1%), mother-only (90.2%), and control group (85%). At month three 85% of babies were exclusively breastfed in the mothers-and-fathers compared to 60% in the control group (p = 0.01). At month three 80% of babies were exclusively breastfed in the mothers-only compared to 60% in the control group (p = 0.04). In the multivariate analysis, babies born to mothers in the mother-and-fathers group were almost five times more likely to be exclusively breastfeed at three months than babies born to mothers who received standard care [AOR: 4.88, 95% CI (1.35,17.63)]. Conclusion An mHealth intervention targeting fathers and mothers, and mothers increased the likelihood of babies being exclusively breastfed at three months. The risk of not exclusively breastfeeding in the control group increased over time. A low-cost SMS-based breastfeeding intervention targeting fathers and mothers showed potential to improve exclusive breastfeeding. Such mHealth interventions could be integrated into the antenatal and postnatal follow-up services provided by midwives. Trial registration This trial was registered with the Australian New Zealand Clinical Trials Registry (ANZCTR) 12,618,001,481,268.